2020
DOI: 10.1370/afm.2571
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Access to After-Hours Primary Care on the Association Between Home Nursing Visits and Same-Day Emergency Department Use

Abstract: PURPOSE Previous work has demonstrated that home care patients have an increased risk of visiting the emergency department after a home nursing visit on the same day. We investigated whether this association is modified by greater access to after-hours primary care. METHODS We conducted a population-based case-crossover study of home care patients in Ontario, Canada in 2014-2016. Emergency department visits after 5:00 pm were selected as case periods and matched, within the same patient, to control periods wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Our finding of higher odds of more frequent ED visits among patients who called the HC for urgent care or afterhours likely indicate urgency of need for advice or care. 10,38,39 Due to the crosssectional nature of our data, it is not clear if the ED visits occurred before the calls or after. In the former case, frequent ED visits may indicate lack of timely access to care.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our finding of higher odds of more frequent ED visits among patients who called the HC for urgent care or afterhours likely indicate urgency of need for advice or care. 10,38,39 Due to the crosssectional nature of our data, it is not clear if the ED visits occurred before the calls or after. In the former case, frequent ED visits may indicate lack of timely access to care.…”
Section: Discussionmentioning
confidence: 98%
“…In the latter case, patients’ calls may indicate seeking primary care to address the health issues that led to the ED visits 7,40 . Past literature about access to after‐hours or urgent care has been inconsistent, with some studies suggesting such access could reduce ED visits while others finding no difference 10,39,41 . For HCs, these findings likely indicate the need for increased capacity for afterhours care and same‐day appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothesizing that these increased ED visits could be reduced when long-term care home residents have access to after-hour primary care, researchers conducted a case-crossover study of residents of Ontario long-term care homes and concluded that increasing afterhours access to primary care could reduce some low acuity visits in this population. 119…”
Section: Limited Inpatient Workforcementioning
confidence: 99%
“…Given these knowledge gaps, the objective of this study was to measure the association between the use of virtual end-of-life care and acute healthcare use (emergency department, hospitalization) and an out-of-hospital death before and after the introduction of specialized fee codes that enabled broader delivery of virtual care during the COVID-19 pandemic. We hypothesized that virtual end-of-life care would be associated with lower rates of acute healthcare use and an increased likelihood of an out-of-hospital death, given that people receiving end-of-life care would have increased access to their physician via virtual care, wanted to avoid unnecessary exposure to SARS-CoV-2 during the pandemic, and generally prefer to die at home [10,[17][18][19]. This study asks a novel research question that helps describe the impact of the COVID-19 pandemic on people at the end-of-life and may prompt further discussion on use-cases for virtual care.…”
Section: Introductionmentioning
confidence: 99%